RANCANG BANGUN MESIN GRANUL PAKAN IKAN DAN UDANG GUNA MENGATASI KENDALA MANDIRI PAKAN - Untag, Asmungi; Lokajaya, I Nyoman (Heuristic, 2014)
Fish and lobster embankment was main occupation of most of Lamongan regency people. So farthey always used fabricated pellet as a fish and lobster food. And this food supplied by broker.There was a dependency between people and broker. This dependency caused problem, thatwas, broker could rise up the price of pellet whenever he wanted. At the other side, the use offabricated pellet in long time will made embankment media in satiation condition. Thiscondition will made many fishes and lobsters died in growth period and the death up to 40%.Gapoktan was a group of people who explored and invented the alternative fish and lobsterfood. This alternative food was made of natural raw material so it reduced the death until 20%.With this alternative food they wanted to be independent in fish and lobster food procurement.They wanted have alternative pellet. But they didn’t have sciences and technologies to make it.This research was designed to overcome their problem. Designing the extruder machine was theanswer of their problem. Designing was done based on the ergonomic concepts. Finally, wasknown this machine capacity up to 672 kg/day. It means that the machine could fulfill theminimum need of fish and lobster food. There were two variance of diameter of pellet, that wasfive and three millimeters with five until ten millimeter long. With this alternative pellet, theycould save 50.8% food procurement cost or equal Rp 6,097/kg.Kata kunci: rancang bangun, mesin granul, pakan ikan dan udang